Preventive maintenance for effective operation of boilers in Kuwait industry - AlAzemi, Ahmed S KH R Q; Che Daud, Mohd Radzi (Transstellar Journal Publications and Research Consultancy Private Limited (TJPRC), 2020)
In this research study, preventive maintenance technique for improving the boiler efficiency is analysed with help of specific methodology. High efficiency can be achieved with the help of an optimal approach of the preventive method. In Kuwait. Among (80) participants, 62.5% of the participants were technical while 37.5% were engineers, the highest group 51.3% were 45 to 55 years old, 51% had master’s degree, 42.5% had more than 10 years as experience and 28.8% working in steel industry. The participants' responses towards the preventive maintenance for efficient operation of boilers had high level with mean score > (3.57) out of (5) according to Likert scale; indicate a high level of agreements. The first rank was (It is required to clean the water side surfaces under preventive maintenance) with the highest mean score 3.9250, indicate that 78.5% of the total participants agreed about it. Last rank is observed (It is required to check the efficiency of boiler routinely by inspecting all major components) with the lowest mean score 3.2500, indicating that only 65% of the total participants agreed about it. Result show that there is a significant difference in the degree of responds towards the preventive maintenance for efficient operation of boilers according to job in favor of engineers group. There is a significant association between job and the following issues which concerned preventive maintenance for efficient operation of boilers, the higher the job as an engineer, the higher the approval score in the following issues:  Preventive maintenance is more useful than other maintenance program.  It is required to purpose an efficient plan/ schedule for preventive maintenance of boiler